Claiming society for God religious movements and social welfare : Egypt, Israel, Italy and the United States - Davis, Nancy J.; Robinson, Robert V. (Bloomington, IN : Indiana University Press, 2012)
Claiming Society for God focuses on common strategies employed by religiously orthodox, fundamentalist movements around the world. Rather than employing terrorism, as much of post-9/11 thinking suggests, these movements use a patient, under-the-radar strategy of infiltrating and subtly transforming civil society. Nancy J. Davis and Robert V. Robinson tell the story of the Muslim Brotherhood in Egypt, Shas in Israel, Comunione e Liberazione in Italy, and the Salvation Army in the United States. They show how these movements build massive grassroots networks of religiously based social service a.
Cover; Contents; Preface; Acknowledgments; INTRODUCTION; 1. CONTESTING THE STATE BY BYPASSING IT; 2. THE MUSLIM BROTHERHOOD: Building a State within a State in Egypt; 3. THE SEPHARDI TORAH GUARDIANS: Penetrating the Israeli State to Circumvent It; 4. COMUNIONE E LIBERAZIONE: Laying the Building Blocks of a Parallel Christian Society in Italy; 5. THE SALVATION ARMY USA: Doing Good to Hasten the Second Coming; CONCLUSION; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based upon print version of record.
Keywords: Religion and sociology; Social Science; Religion; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Religion and sociology; Electronic books